OPTIMALISASI PENGGUNAAN TEKNOLOGI TEPAT GUNA DI ERA DIGITAL - Alwi, Muhammad Alwi; Haslinda, Haslinda; Yunus, Kartini; Fahar, Abustan; Arfah, Arfah (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
Community service activities aim to provide understanding to the public regarding the optimizationof the use of appropriate technology in the digital era. The implementation of community service activities usesthe lecture and discussion method which is carried out in 2 stages, namely the stages of service planningactivities, and the stages of implementation activities in Samalewa village, Bungoro District, Pangkep district.In addition, the implementation of this activity has gone smoothly and the community has welcomed thisactivity.